2022
DOI: 10.3390/ijerph19031106
|View full text |Cite
|
Sign up to set email alerts
|

Non-Epithelial Ovarian Cancers: How Much Do We Really Know?

Abstract: Non-epithelial ovarian cancers (NEOC) are a group of uncommon malignancies that mainly includes germ cell tumours (GCT), sex cord-stromal tumours (SCST), and some extremely rare tumours, such as small cell carcinomas and sarcomas. Each of these classifications encompasses multiple histologic subtypes. The aetiology and molecular origins of each sub-group of NEOC require further investigation, and our understanding on the genetic changes should be optimised. In this article, we provide an update on the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 97 publications
0
43
0
2
Order By: Relevance
“…The preoperative diagnosis of OMMMT is difficult because it does not have specific tumor markers and imaging features. Some diagnostic work-up methods including pelvic ultrasound, abdominal-pelvic computed tomography (CT), chest X-ray and positron emission tomography (PET) scans are still necessary for the diagnosis of ovarian cancer [ 28 ]. Although the images features are not sufficient for diagnosis, the detailed clinical and imaging features may be helpful to improve the familiarity of this rare tumor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative diagnosis of OMMMT is difficult because it does not have specific tumor markers and imaging features. Some diagnostic work-up methods including pelvic ultrasound, abdominal-pelvic computed tomography (CT), chest X-ray and positron emission tomography (PET) scans are still necessary for the diagnosis of ovarian cancer [ 28 ]. Although the images features are not sufficient for diagnosis, the detailed clinical and imaging features may be helpful to improve the familiarity of this rare tumor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in terms of the non-EOC, a subset of germ-cell tumours can acquire KRAS -activating mutations and other genetic alterations, such as BRCA1/2 , KIT , and MAPK . However, the efficacy of targeted therapy and genomic features contributing to chemoresistance still remain to be elucidated [ 74 ]. Similarly, even though the rate of BRCA1 and BRCA2 mutations in ovarian carcinosarcomas is difficult to be determined, the genomic sequencing in some studies has demonstrated loss of function mutations in HR genes.…”
Section: Susceptibility To Eocmentioning
confidence: 99%
“…In contrast, low-grade serous tumours are characterised by KRAS, BRAF, PTEN, PIK3CA, CTNNB1, ARID1A, and PPP2R1A mutations and progress according to the type I pathway [9]. Beyond EOC, there are also non-epithelial counterparts that are further divided into germ cell (5%) and sex-cord stromal cell (5%) ovarian cancers [10][11][12]. Ovarian 2 of 14 carcinosarcoma is even rarer; it is a biphasic, but challenging histologic subtype, accounting for only 1-4% of all ovarian cancers [13].…”
Section: Introductionmentioning
confidence: 99%